Studi Pemain Basket Samuel Pelmelay dalam Membangun Personal Branding Rookie of the Year Indonesian Basketball League (IBL) - Shandy Axel Natanael; Farid Rusdi (Prologia, 2020)
Personal branding is imagery oneself to a be seen by the prices of other commodities appear others, how do we promote in cunning and oppression in what we would like to achieve them. Of the west a strategy is the process of the determination of a plan of the market to hold the leader of the top of the namely you focus on the long term goals with the, and with these levites were the preparation of a way worthy of or effort of how to make the purpose of the figure was reached. Samuel was done by a guy new players (rookies) ripped through a crowded have been on the talk among the league as the highest and the of  Indonesia basketball league, because through Samuel had managed to develop into nominations new best players (rookies of the year). Was used in the study a qualitative approach by a method of interviewing of resource persons who become a fan from Samuel.This study used a qualitative approach by a method of interviewing speakers who became a fans of Samuel. The research showed samuel promoting him from humble to fans, trying to professional basketball teams in direct and in life, having integrity to trusted by everybody and can be responsible for everything, more open to fans to share experiences which have so far been in a can, and consistent suitor to continuous if anything can be fix.Personal Branding adalah citra diri yang dilihat oleh orang lain terlihat orang lain, bagaimana kita mempromosikan diri kepada orang yang kita ingin capai. sedangkan pengertian strategi adalah proses penentuan rencana pa pemimpin puncak yang berfokus pada tujuan jangka panjang, disertai penyusunan suatu cara atau upaya bagaimana agar tujuan tersebut tercapai. Dalam penelitian ini, penulis menggunakan teori Personal Branding, Konsep Personal Branding, dan Kriteria Personal Branding.Samuel adalah seseorang pemain baru (Rookie) yang ramai dibicarakan pada kalangan liga tertinggi yaitu Indonesia Basketball League (IBL), karena Samuel masuk dalam nominasi pemain baru terbaik (Rookie of The Year). Penelitian ini menggunakan pendekatan kualitatif dengan metode wawancara terhadap narasumber yang menjadi penggemar (fans) dari Samuel. Hasil penelitian menunjukkan Samuel mempromosikan dirinya mulai dari sikap yang baik (Humble) terhadap penggemar, mencoba profesional di dalam Tim Basket maupun dalam kehidupan langsung, memiliki integritas supaya dapat dipercayai oleh semua orang dan bisa bertanggung jawab atas segala sesuatu, lebih terbuka terhadap penggemar agar berbagi pengalaman yang selama ini sudah di dapat, dan mempunyai sikap konsisten supaya bisa terus menerus jika ada yang salah bisa di perbaiki.